MEMBANGUN INTELEKTUAL SANTRI MENUJU KARAKTER MUSLIM SEJATI - Fauzi, Ahmad (LP3M Universitas Al-Qolam Malang, 2023)
The aim of this research is to conduct how santri’s intellectual concept being developed as the well as it becomes a relevant characteristic. This research is also determined to respond two primary issues faced by Islamic religion in Indonesia nowadays. It constitutes the resurgence of intellectual traditions and the emergence national moderation modus. The findings of this study indicate that firstly the Islamic pesantren sufism consistently sustains Indonesian Islamic intellectual traditions, that is the implementation and development of Islamic curriculum based on Asy’ari-Maturidi, a doctrine developed from Al Qur’an. Besides that, a significant decrease in education quality in rural areas, which is induce the appearance of pesantren sufism. Then, pesantren sufism reacted to the recent educational institutions taught by its alumna. As the results of the consistency of institutional Islamic education, pesantren sufism play a main role in religious moderation. Key words: intellectual; Islamic education; moderation; pesantren; sufism